Student's Perceptions about Pediatric Dental Behavior Guidance Techniques throughout a five-year Dental Curriculum - Dutra de Oliveira, Rosa Virginia [UNESP]; Barbosa Angelo, Anna Carolina; Araujo Brito, Deborah Brindeiro de; Gomes de Medeiros, Rubenia Cristina; Soares Forte, Franklin Delano; Sousa, Simone Alves (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2015)
Objective: To compare students' views about behavior management techniques (BMT) in pediatric dentistry, besides to identify whether educational components of dental curriculum may influence their perceptions. Material and Methods: Questionnaires with 18 statements, describing the techniques and clinical situations were distributed to students (n=83) from first- (P1), third- (P2) and eighth- (P3) semesters. Student's acceptability scores were measured with a Likert scale from 0 (total disagreement) to 10 (total agreement). Statistical analysis was performed using Mann Whitney U test. Results: P3 students agreed with most of BMTs. Pair comparisons between P1-P2 showed significant increase of means for Told treatment may involve pain and Sedative, besides significant decrease for Use of euphemisms. Comparisons between P2-P3 and P1-P3 indicated significant increase in the acceptability for: Voice control, Told not to be coward, Modeling, Blunting, Use of euphemisms, Parent not present, HOME, Active and Passive Immobilization and pharmacologic techniques. In all semesters, Verbal positive reinforcement, Distraction and Tell-show-do were the most accepted techniques, however, there was no consensus regarding to the least accepted one. Promising a toy became less acceptable throughout the semesters and Parent not present became more acceptable. Conclusion: These findings indicate that educational process may influence on the students' perceptions about BMTs.
Keywords: Dental Education; Pediatric Dentistry; Child Behavior